Physicochemical properties of acylated low molecular weight chitosans - Tiew, Shu Xian; Misran, Misni (Taylor & Francis, 2018)
Hydrophobically modified chitosans are developing progressively in drug delivery system due to their ability to encapsulate drugs with the amphiphilic architecture. In this study, low molecular weight chitosans were acylated with hexanoyl (LCh-C6), octanoyl (LCh-C8) and decanoyl (LCh-C10) groups to study their physicochemical properties for the potential as drug carriers. Both fourier transform-infrared (FT-IR) and 1H NMR (Nuclear Magnetic Resonance) analyses confirmed the successful acylation of alkyl chains onto chitosan backbone. LCh-C6, LCh-C8 and LCh-C10 showed the similar value of critical aggregation concentration around 40 µg L−1. The average particle size of LCh-C6, LCh-C8 and LCh-C10 obtained by dynamic light scattering measurement was compared to by mean of transmission electron microscopy. Acylated low molecular weight chitosans (LChA) showed higher encapsulation efficiency and drug loading toward hydrophobic salicylic acid as compared to hydrophilic caffeine, as well as exhibited higher increment in particle size due to possible inner volume expansion. Both long alkyl chains and high degree of substitution contributed to better drug encapsulation of LChA.